Evaluation of diabetes care management in primary clinics based on the guidelines of American Diabetes Association - Albarrak, Ahmed I.; Mohammed, Rafiuddin; Assery, Bushra; Allam, Dalya; Al Morit, Sarah; Al Saleh, Reem; Zare’a, Reem (International Journal of Health Sciences, 2018)
Objective: There is a rapid increase in the incidence of diabetes mellitus in Saudi Arabia. Diabetes management is an essential constituent to prevent prognosis of diabetes complications. The main objective of this study was to assess diabetes care in primary clinics based on the guidelines of American Diabetes Association (ADA). Methods: A retrospective study at King Khaled University Hospitals (KKUH), Riyadh, Saudi Arabia. A total of 200 patients were randomly selected from the databases of primary care clinics. An evaluation checklist was created based on the ADA treatment guidelines such as medical history, physical examination, laboratory evaluation and referrals. Results: The result showed that elements achieving the ADA targets for overall care were medical history (44.9%), physical examination (59.6%), laboratory evaluation (36.3%) and referrals (19.3%). The other sub elements indicators such as referral to diabetes self-management education clinics (10%), dental examination (2%), HbA1c regular monitoring (33.5%) and blood pressure determination (100%) were documented with adherence to ADA standards. Conclusions: Diabetes management standards is an essential element in the success of the management plan. Most of the elements examined are not in full compliance with the ADA standard. Continues monitoring and self-review is recommended.